(untitled) (International Journal of Innovative Technologies in Economy, 2025)
Effective operational cost management is a critical concern for enterprises striving to maintain competitiveness while advancing sustainable development goals. This study investigates how non-state enterprises in Kazakhstan manage operating expenses in alignment with sustainability principles, particularly emphasizing the potential of blockchain-supported multiple offsetting systems. A cross-sectional mixed-methods design combined survey responses from 43 professionals across key industries with qualitative data from 15 structured interviews. Survey results indicate that most enterprises maintain a strong cost-monitoring culture (87% agreement), yet only moderate integration of sustainability in operational decision-making (71%). Awareness of blockchain-based cost optimization remains limited (43%), although 66% of respondents expressed openness to exploring blockchain-enabled financial settlements. A multiple linear regression model was estimated to identify drivers of blockchain readiness. The analysis revealed that cost strategy sophistication (β = 0.562, p < 0.01) and sustainability orientation (β = 0.391, p < 0.05) were statistically significant predictors, together explaining 41% of the variance in blockchain adoption readiness (Adjusted R² = 0.41, p < 0.001). Qualitative findings reinforced these insights, revealing themes around decentralized cost-sharing, blockchain’s potential to improve inter-enterprise trust, and concerns over implementation complexity and regulatory uncertainty. The study concludes that while blockchain-based offsetting systems offer scalable, cost-effective solutions, successful adoption depends on technical training, policy incentives, and broader institutional support.